Functional Involvement of Dual Specificity Phosphatase 16 (DUSP16), a c-Jun N-terminal Kinase-specific Phosphatase, in the Regulation of T Helper Cell Differentiation - Musikacharoen, Tipayaratn (American Society for Biochemistry and Molecular Biology, 2011)
Naïve CD4(+) T helper (Th) cells differentiate into distinct subsets of effector cells (Th1, Th2, Th17, and induced regulatory T cells (iTreg)) expressing different sets of cytokines upon encounter with presented foreign antigens. It has been well established that Th1/Th2 balance is critical for the nature of the following immune responses. Previous reports have demonstrated important roles of c-Jun N-terminal kinase (JNK) in Th1/Th2 balance, whereas the regulatory mechanisms of JNK activity in Th cells have not been elucidated. Here, we show that dual specificity phosphatase 16 (DUSP16, also referred to as MKP-M or MKP-7), which preferentially inactivates JNK, is selectively expressed in Th2 cells. In the in vitro differentiation assay of naïve CD4(+) cells, DUSP16 expression is up-regulated during Th2 differentiation and down-regulated during Th1 differentiation. Chromatin immunoprecipitation revealed the increased acetylation of histone H3/H4 at the dusp16 gene promoter in CD4(+) T cells under the Th2 condition. Adenoviral transduction of naïve CD4(+) T cells with DUSP16 resulted in increased mRNA expression of IL-4 and GATA-3 in Th2 and decreased expression of IFNγ and T-bet in Th1 differentiation. In contrast, transduction of a dominant negative form of DUSP16 had the reverse effects. Furthermore, upon immunization, T cell-specific dusp16 transgenic mice produced antigen-specific IgG2a at lower amounts, whereas DN dusp16 transgenic mice produced higher amounts of antigen-specific IgG2a accompanied by decreased amounts of antigen-specific IgG1 and IgE than those of control mice. Together, these data suggest the functional role of DUSP16 in Th1/Th2 balance.